The Role of Physical Exercise in the Prevention of Musculoskeletal Disorders in Manual Workers: A Systematic Review and Meta-Analysis - Bullo, Valentina; Favro, Francesco; Pavan, Davide; Bortoletto, Alessandro; Gobbo, Stefano; De Palma, Giuseppe; Mattioli, Stefano; Sala, Emma; Cugusi, Lucia; Di Blasio, Andrea; Cruz-Diaz, David C.; Sales Bocalini, Danilo; et al. (La Medicina del Lavoro, 2024)
Work-related musculoskeletal disorders (WMSDs) are the most common occupational health problem in the European Union. Physical exercise interventions have been investigated in the prevention of WMSDs in many sectors. Therefore, our aim was to assess the effect of physical exercise in manual workers for the primary and secondary prevention of WMSDs. We conducted a systematic search of the literature and papers were included if: the participants were adult employees exclusively engaged in manual labor tasks; non-acute physical exercise intervention; pain, disability, physical functioning, or health-related quality of life outcome, with pre-post intervention measurements. We retrieved 10419 unique records and included 23 studies. A random effect meta-analysis was conducted on the studies with a control group design, using a three level model to estimate the pooled effect for pain outcomes (g = 0.4339, 95% CI : 0.1267 – 0.7412, p < 0.01), and a two-level model for disability outcomes (g = 0.6279, 95% CI : 0.3983 – 0.8575, p < 0.0001). Subset analysis revealed a moderate-to-large effect on the VAS outcome (g = 0.5866, 95% CI: 0.3102 – 0.8630, p < 0.0001). Meta-regression on pain outcomes revealed a significant effect for sex, age, study quality, and body segments tested. The analyses on all outcomes except VAS showed substantial heterogeneity (I2pain = 93%, of which 72% at the study level, I2disability = 78%, and I2vas = 56%, of which 44% at the study level). Physical exercise programs seem to have a positive effect on pain and disability stemming from WRMSDs in manual workers.